The regulation of prostitution in China : law in the everyday lives of sex workers, police officers, and public health officials / Margaret L. Boittin. - Boittin, Margaret L., 1979- (Cambridge studies in law and society., 2024)
In this compelling book, Margaret L. Boittin delves into the complex world of prostitution in China and how it shapes the lives of those involved in it. Through in-depth fieldwork, Boittin provides a fascinating case study of the role of law in everyday life and its impact on female sex workers, street-level police officers, and frontline public health officials. The book offers a unique perspective on the dynamics between society and the state, revealing how the laws that govern sex work affect those on the frontlines. With clear and accessible prose, this book is a must-read for anyone interested in law, state-society relations, China, and sex work.